PERSEPSI WISATAWAN TERHADAP AKUN MEDIA SOSIAL INSTAGRAM @WATUAMBEN - K, Nuharani Erningdyah; Rahmawati, Dessy (JURNAL MEDIA WISATA: Wahana Informasi Pariwisata, 2018)
Natural tourism destinations Watu Amben is tourist destinations which presents a panorama of the natural landscape which is located in the village of Pandeyan, district Piyungan, Bantul. One of the efforts made by the Manager of Watu Amben to introduce these tourist destinations to the public is using social media Instagram. Based on the foregoing, the researchers conducted a study with the title "Tourist Perception of Social Media Account Instagram@watuamben". Research methods used in this research is qualitative research. This research was conducted in nature tourism Watu Amben, with data collection techniques observation, interview, questionnaire and the documentation. The interviews addressed to account manager Instagram @watuamben and also tourists coming to Watu Amben, while questionnaires addressed to tourists visiting the Watu Amben. The purpose of this research is to know the visitor's perception of social media account Instagram @watuamben. The result of this research is that the pictures or videos that uploaded in Instagram by @watuamben could change the tourist perspective about tour destination waktu ambrn when they see the pictures and the videos. Also, the researchers hope that the administrators of Instagram account @watuamben could use the media social to introduce the tour destination watu amben to public effectively. Keywords: Tourists Perception, Social Media, Instagram, Watu Amben